Pseudo-Gaze Deviation Resulting From Positive Angle Kappa and Esotropia. Issue 2 (June 2021) - Rateaux, Maxence; Espinasse-Berrod, Marie-Andrée; Couret, Chloé; Bremond-Gignac, Dominique; Robert, Matthieu P.
Abstract : Abstract: A 6-year-old boy was referred for constant right gaze deviation. Rather than a gaze deviation, he constantly seemed to look on the left side of any displayed target. Examination revealed the association of a highly positive angle Kappa and an esotropia of equal values. He also exhibited signs of ocular albinism with no associated infantile nystagmus syndrome. The X-linked ocular albinism was confirmed genetically, explaining the presence of a positive angle Kappa. A highly positive angle Kappa can be associated with a convergent strabismus; in case both values offset each other, this can result in a constant "sidelooking, " which should not be confused with a gaze deviation.